1999
DOI: 10.1136/ip.5.4.294
|View full text |Cite
|
Sign up to set email alerts
|

Pre-hospital emergency medical services: a population based study of pediatric utilization

Abstract: Objectives-To examine emergency medical services (EMS) usage by children in one state. Methods-Dispatch of an EMS vehicle in response to a call in the US is referred to as a "run". Runs for Utah for 1991-92 were linked to corresponding hospital records. Abbreviated injury severity scores (AISs) were assigned using ICDMAP-90 software. Results-For the two year period there were at least 15 EMS runs per 100 children per year, with incomplete reporting from rural areas. EMS response and scene times were similar fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 14 publications
(5 reference statements)
1
19
0
Order By: Relevance
“…look closer at the effect of age, we adjusted for specific insurance types and found that older children without insurance have increased odds of ambulance use, similar to adult studies. One possible explanation for the difference in use by age is the higher incidence of injuries, poisoning and mental health problems in the older age group; all of which are associated with higher rates of ambulance use [15,20,25].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…look closer at the effect of age, we adjusted for specific insurance types and found that older children without insurance have increased odds of ambulance use, similar to adult studies. One possible explanation for the difference in use by age is the higher incidence of injuries, poisoning and mental health problems in the older age group; all of which are associated with higher rates of ambulance use [15,20,25].…”
Section: Resultsmentioning
confidence: 99%
“…Most pediatric ambulance studies have utilized data from individual hospitals or statewide databases and very few have examined the effect of insurance on ambulance use [13][14][15][16]. Some studies that focus on adults have suggested that those patients without insurance or public insurance view the ambulance as a "taxi service" since they do not see a bill Other studies that focus on adults suggest that the utilization pattern is multifactorial [8,9,[17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…EMTparamedics generally respond to more calls in a typical week (18.4 calls versus 4.2 calls for EMT-basics) [29], which may further explain the contribution of practice level to the experience of violence among EMTs. Additionally, EMTparamedics treat more severely injured patients [30,31] and have the opportunity to support law enforcement personnel during dangerous deployments such as hostage situations and drug raids [32]. These situations may also increase the likelihood of EMT-paramedics experiencing violence.…”
Section: Discussionmentioning
confidence: 99%
“…When children younger than 5 years are cared for in the EMS system, they are less likely to receive appropriate interventions, such as splinting or cervical spine immobilization. 3 According to the 2000 US Census,* 42% of the population lives in nonmetropolitan areas, 25% of which are rural 4 ; 41% of community hospitals are considered rural by the American Hospital Guide. 5 Additionally, certain populations such as Native Americans disproportionately live in rural areas.…”
Section: Introductionmentioning
confidence: 99%